Analysis of thrust force generation during the drilling of natural fiber based hybrid composite - Mohan Kumar Anand Raj; Rajasekar Rathanasamy; Parameshwaran Rathinasamy; P. Manoj Kumar; Sureshkumar Periyasamy; Ahmad Aziz Alahmadi; Mamdooh Alwetaishi; Parvathy Rajendran; It Ee Lee (Scientific Reports)
Abstract In this study, thrust force generation during drilling in natural fiber-reinforced epoxy has been investigated. Three natural fibers Abaca (A), Hemp (H) and Jute (J) have been utilized. Four different point angles of the twisted drill tools have been employed: 90°, 100°, 105° and 118°. The sequence of natural fiber-based specimens prepared for the studies as follows: A/H/A/H and H/J/H/J. The objective of this study is to find the drilling process parameters at lower thrust force. Also find the percentage of contribution of the drilling process parameters on the thrust force. Few authors has studied the drilling analysis using angle variation in the twisted drill bit however, no researches has been found in the drilling study of Hemp, Abaca and Jute by different angled twist drill bit. The result indicates that at 0.05 mm/rev feed rate and 3000 rpm spindle speed generated minimum thrust force of 4.6 N on abaca and hemp-based composites using 90°-point angle of the twisted drill bit. At 0.05 mm/rev, 3000 rpm and 90°-point angle of drill bit, produced minimum thrust force of 3.1 N on Hemp and Jute fiber-based composite. Thermal imager has been used to monitor temperature variation during the drilling of composite specimens. Defects in the specimen was identified by using scanning electron microscopic and microscopic images. The analysis of variance of the thrust force generated during drilling of the A/H/A/H and H/J/H/J based composite materials has performed using Minitab 21 software.